EVALUASI PEMENUHAN STANDAR TEKNIS FASILITAS PEJALAN KAKI PADA KAWASAN KUANINO KUPANG - Krisantus Satrio Wibowo Pedo (Program Studi Teknik Sipil Universitas Katolik Widya Mandira, 2022)
The Kuanino area in Kupang City is an area that is dense with goods and services trading activities. The ease of access to this area is supported by various existing transportation infrastructure facilities. One thing of concern is access to pedestrian infrastructure, which often gets the last priority in the development of road transport infrastructure. Pedestrian facilities can be said to be good if they meet technical planning standards that accommodate all levels of society, including people with disabilities. The purpose of this study was to evaluate the fulfillment of existing pedestrian facilities to the minimum technical service standards based on applicable regulations and guidelines. The research method uses an evaluation of the existing condition of pedestrian facilities against the standard criteria for pedestrian facilities. 03/PRT/M/2014. The results of the study show that the safety aspects (height differences and guiding tiles for people with disabilities), accessibility (disruption to the sidewalk), connectivity (crossing facilities) and support still do not meet the technical standard criteria, so it is necessary to improve pedestrian facilities on Jl. Gen. Sudirman (Kuanino) based on the 3E model, namely engineering, education and enforcement.